Cryptolepis buchanani oil formulation versus indomethacin solution in topical therapy for osteoarthritis of the knee: A randomized controlled trial - Nutthiya Hanprasertpong (2018)
© 2017 Elsevier GmbH Aim This study aimed to compare the efficacy of a topical Cryptolepis buchanani oil formulation (CBO) with indomethacin, a topical non-steroidal anti-inflammatory drug, in the symptomatic treatment of osteoarthritis (OA) of the knee. Study design This study was a randomized, double-blind, active-controlled trial. Methods One hundred and sixty-nine patients with OA of the knee were randomly assigned to receive either a 1% indomethacin solution or CBO formulation, which were applied topically, four times a day for a period of four weeks. Clinical assessments included a visual analog scale (VAS) assessment of joint pain, VAS assessment of stiffness, Lequesne's functional index (LI), time taken to climb up 10 steps, and patient's and physician's opinions of overall improvement. Results After four weeks of treatment, there were no statistically significant differences between the two groups in mean changes from baseline of the VAS assessment of total pain (p = 0.92), VAS assessment of total stiffness (p = 0.57), LI (p = 0.44), and time taken to climb up 10 steps (p = 0.61). Additionally, the mean VAS of patient's and physician's opinions of overall improvement did not differ significantly (p = 0.77 and p = 0.77, respectively). The percentages of responders in the CBO and the indomethacin groups were also comparable (67.44% versus 69.88%, p = 0.86). Treatments were generally well tolerated, with reports of pruritus and rash at the application site occurring significantly more frequently in the indomethacin than CBO group (28.92% versus 10.47%, p = 0.005 and 21.69% versus 8.14%, p = 0.024, respectively). Conclusion CBO was as effective as indomethacin solution for the symptomatic treatment of OA of the knee, but had a significantly lower rate of adverse skin reactions.